Zingiber ultralimitale subsp. matarombeoense Ardiyani & Ardi (Zingiberaceae), a new subspecies from Sulawesi - Ardiyani, Marlina; Ardi, Wisnu H.; Santoso, Wahyudi (Phytotaxa, 2021)
A new subspecies of Zingiber ultralimitale Ardiyani & A.D.Poulsen was found at Matarombeo, South-East Sulawesi. Zingiber ultralimitale subsp. matarombeoense Ardiyani & Ardi, was described, illustrated and barcoded using four barcoding loci (rbcL, trnH-psbA, Internal Transcribed Spacer-ITS, and matK). Provisional conservation status assessment indicates a Critical Endangered (CR) status. The taxonomic placement into section was determined based on morphology, molecular, and pollen SEM data.